Analysis of Biological Factors that Influence the Acceleration of Menarche in Female Students Aged 13-14 Years - Nursitiyaroh; Evi Wardah Kusumah; Nia Komalasari; Rizawati; Rizky Fessa Vandhe; Silvia; Siska Meryani; Tuti Alawiyah; Wiwik Norkhotijatul Fitriyah (Jurnal Penelitian Pendidikan IPA, 2024)
Various biological factors influence the acceleration of the age of menarche in female students aged 13-14 years. These factors include exposure to pornographic media, excess body weight, consumption of fast food, nutritional status, history of maternal age at menarche, sexual knowledge, height, and family economic status. Early exposure to sexual content and a high-fat diet can accelerate sexual maturity through changes in hormone production, while nutritional status and history of maternal age at menarche are also associated with accelerated menarche. This research involved 85 class VII female students who were selected purposively to analyze the influence of these factors on the age of menarche. Data was collected through questionnaires and physical measurements, then analyzed using the Chi-square test. The results show that exposure to pornographic media, excess body weight, consumption of fast food, nutritional status, and history of the mother's age at menarche have a significant influence on accelerating the age of menarche (p-value < 0.05). On the other hand, height, sexual knowledge and family economic status did not have a significant effect (p-value > 0.05). It is recommended that parents and schools limit teenagers' access to pornographic media and encourage healthy lifestyles to prevent acceleration of the age menarche.